Knowledge, attitude and practice on cervical cancer screening and human papillomavirus vaccination among adolescent girls residing in a slum of Kolkata - Das, Adwitiya; Sarkar, Suhena; Nawal , Harsh; Sil , Debopam; Mohta, Sakshi; Banerjee, Ankush (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Cervical cancer has emerged as an important public health concern among Indian women as it contributes to significant mortality. Early diagnosis and its prevention are thus of vital importance in the current scenario. This study assessed the knowledge, attitude, and practice regarding screening and human papillomavirus vaccination among adolescent girls in a slum area of Kolkata. Methods: This cross-sectional study was conducted among 227 adolescent girls (aged 14–19 years) at Arpuli Lane, Kolkata. A pre-designed questionnaire was used for data collection. Chi-square test and binary logistic regression analysis were done to findout the factors associated with knowledge, attitude and practice. Results: Approximately 91% had inadequate knowledge regarding the prevention of cervical cancer, 47% had an unfavourable attitude towards the prevention of cervical cancer, and 22% had undergone a Pap smear examination/HPV test, while only 13% had received HPV vaccination. The educational status of the participants and their mothers was significantly associated with knowledge, attitude, and practice regarding cervical cancer screening and HPV vaccination. Conclusion: Appropriate behaviour change communications should be initiated considering the propensity for high-risk behaviour and poor knowledge and attitude. Future studies should reveal the causes of their poor behaviour to ensure timely screening and adequate vaccine coverage.